FINANCIAL AND ECONOMIC SECURITY OF AGRICULTURAL ENTERPRISES (International Journal of Innovative Technologies in Economy, 2018)
The author studies the essence of financial and economic security of agricultural enterprises in the context of current changes in the economic situation in the country. The author also proves that the company’s transition towards sustainable development, which is supported by the system of its financial and economic security, allows for differentiation in the targets of such system both in short and long terms.